Human antibody 3E1 targets the HA stem region of H1N1 and H5N6 influenza A viruses - Wenshuai Wang (Nature Portfolio, 2016)
Treatment of influenza A viruses with broadly neutralizing monoclonal antibodies is an area of active research. Here, the authors characterise a human monoclonal antibody called 3E1 that was reactive against both H1 and H5 viruses in vitroand demonstrated some treatment efficacy in mice.